Intraocular Pressure Changes After Rhinoplasty: A Before‐and‐After Cross‐Sectional Study - Ali Goljanian Tabrizi; Matin Ghazizadeh; Atiyeh Zahedi (Health Science Reports)
ABSTRACT Background and Aims Rhinoplasty, a prevalent cosmetic surgery, often involves lateral osteotomy, which can lead to ocular complications such as edema and ecchymosis. A potential complication is increased intraocular pressure (IOP) postoperatively. This study aims to investigate the impact of lateral osteotomy during rhinoplasty on IOP in patients. Methods This prospective before‐and‐after cross‐sectional study evaluated the effect of lateral osteotomy during rhinoplasty on IOP in 96 patients. Preoperative ophthalmologic examinations included best‐corrected visual acuity, slit lamp biomicroscopy, Goldmann tonometry, and dilated fundoscopy. IOP measurements were taken three times per eye at baseline, during surgery, on the first postoperative day, after nasal pin removal on the seventh postoperative day, and on the thirtieth postoperative day using a Goldmann tonometer. The mean IOP was recorded at each time point. Results The study found no significant changes in IOP at 1, 7, or 30 days postsurgery (p = 0.194). Additionally, the type of surgery did not significantly affect ocular internal pressure (p = 0.622). Conclusion Rhinoplasty with lateral osteotomy appears to be safe concerning IOP. However, monitoring IOP during rhinoplasty is advisable.